1998
DOI: 10.2514/2.5338
|View full text |Cite
|
Sign up to set email alerts
|

Technology and Application Aspects of Applied Field Magnetoplasmadynamic Propulsion

Abstract: Currently available or realizable applied eld magnetoplasmadynamic (AF -MPD) thrusters operating in the power range 5 -100 kW appear to be excellently suited for orbit change and stationkeeping (drag compensation) of large satellites because of their high speci c impulse, suf cient thrust, and compact geometry. They were developed to considerable maturity almost 20 years ago, but have not yet been used in space because of the lack of missions, appropriate power, and quali cation. There is evidence that these e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…1(b). Four major acceleration modes are considered to be effective; [19][20][21] briefly, the four modes are as follows:…”
Section: A Acceleration Modelmentioning
confidence: 99%
“…1(b). Four major acceleration modes are considered to be effective; [19][20][21] briefly, the four modes are as follows:…”
Section: A Acceleration Modelmentioning
confidence: 99%
“…From the inception of the magnetic nozzle 1 (MN), there has been a growing interest in their capability to accelerate a plasma "contactlessly" in advanced electric propulsion. Examples of next-generation plasma thrusters based on MNs that are actively being developed include the Helicon Plasma Thruster 2,3 (HPT), the Electron-Cyclotron-Resonance thruster 4,5 (ECRT), the Applied-field MPD thruster 6 (AF-MPDT), and the Variable Specific Impulse Rocket (VASIMR). 7 In the usual design, a MN consists in an axisymmetric, divergent magnetic field that guides the supersonic expansion of a hot plasma jet.…”
Section: Introductionmentioning
confidence: 99%
“…2 Due to the external source of magnetic field, AF-MPD thrusters have the advantages over SF-MPD thrusters because desirable electromagnetic accelerations are possible for a lower power level, below 100 kW. 3 The applied magnetic field is normally produced by an external coil surrounding the anode, and a variety of field configurations can be applied by changing the coil position or the coil current. Research has shown that it may be advantageous to operate MPD thrusters with axial and radial magnetic fields.…”
mentioning
confidence: 99%